Better off undead - Preller, James (New York : Feiwel and Friends, 2017)
Adrian Lazarus, who became a zombie just before starting middle school, and new friends Gia, Zander, and Talal, navigate a mystery involving global warming, disappearing bees, and billionaire developers.
Keywords: Zombies -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Bees -- Fiction; Environmental protection -- Fiction; Adventure and adventurers -- Fiction; Mystery and detective stories